A Framework For Accessing Patient Health Records Using Information Communication Technology Devices - Mohd Yaacob, Noorayisahbe (2016)
Health is an important aspect of life’s well-being. Thus, it is important that the provision of healthcare is allowed and make it easy for patient to access their respective personal health records at any time and at anywhere. Electronic personal health record (e-PHR) can be defined as one of the important role in management of human life which provide patient to access and manage their medical at any time and at anywhere. However, a few gaps have been identified in the patient self-management. The first gap is the crucial personalize health records (PHR) attributed to be viewed by the patient. The second gap is the data integrity patient privilege-which meant provide the ability for the patient to delete information from the e-PHR or withhold the communication of certain information. Nevertheless, this capability is built into most e-PHRs by having this privilege-made personalized information not valid and leading to data manipulation. The aim of this research is to solve problem in patient self-management of e-PHR by capturing some limitations which are crucial PHR attributes and data integrity of PHR. The processes of this research started by identify the crucial dataset represent PHR attribute via surveys and interviews with medical experts to understand the crucial PHR attribute. Subsequently, by perform a comparison of current and previous studies on healthcare system architecture. The data collection of this research was done through several approaches via interviews, online surveys, questionnaires, literature reviews and observations. The primary data were collected using semi-structured and open-ended interviews and were combined with observations and analyses of the organization's documents. Meanwhile, secondary data were gathered from the literature review and organization documents that formed the theoretical and initial proposed framework. Finally, as a result, the design of conceptual and deployment model of proposed framework was produced and a prototype system (e-PHR) was developed to validate the proposed framework. The validation of this research consisted two parts which are validation of proposed framework architecture from software aspect and validation through user satisfaction aspect. The validation of the proposed framework architecture was done through interviews on few important criterions with the software expert from two companies based in Malacca. The result of validation of architecture for proposed framework part is precise. While, for the viability aspect was flexible and enabled the personal health record to be accessed anytime and anywhere by the patient through the multi devices and can be kept into storage devices. The implementation aspect was supported and recommended to be implemented not in UTeM but also in the entire private or government Health Centers in Malaysia. Additionally, the validation from the user satisfaction measured from few important aspects through surveys conducted at UTeM the target users is the UTeM staff including UTeM student in different faculties. As a result, 87.6% users agreed of the system capabilities. 83.2% users agreed with overall performance expectancy. 86.7% users agreed and were satisfied to use this system. In conclusion, this research was conducted through case study approach at the UTeM Health Centre. The findings and validation showed that this framework is suitable to be implemented especially in Malaysia. Besides that, these research outcome have provide improvement and benefits in the field of electronic personalize health records where patient as user’s are able to access and manage their own personal health records by themselves through the proposed framework via multi devices such smart phones, tablets, personal computers and laptops as well as to keep in local, cloud and centralized storages.